2023
DOI: 10.33899/ijvs.2022.133902.2321
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant and clonal dispersion of enterotoxigenic Escherichia coli from ready-to-eat meat products in Duhok province, Iraq

Abstract: This research evaluated the effluent proportion of E. coli and ETEC in RTE meat products, characterized the isolated strains' clonal relatedness, and determined their antibiotic resistance. 130 RTE products were gathered from various restaurants and street fast food vendors in Duhok and Zakho Province. The Isolates of E. coli identified by culture methods were confirmed as ETEC by multiplex PCR of the identified virulence genes. ERIC-PCR was applied to establish the clonal relationships between strains. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
15
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 38 publications
11
15
3
1
Order By: Relevance
“…Aynadis and Engdawork (23) in Southern Ethiopia revealed that the isolation of E. coli done by taking swab samples from the skin of Cyprinus carpio was 32.5%. Our study's results also agreed with Taha and Yassin's findings (24) when they studied Cyprinus carpio fish in Dohuk province, Iraq, where they obtained 39.1%.…”
Section: Discussionsupporting
confidence: 92%
“…Aynadis and Engdawork (23) in Southern Ethiopia revealed that the isolation of E. coli done by taking swab samples from the skin of Cyprinus carpio was 32.5%. Our study's results also agreed with Taha and Yassin's findings (24) when they studied Cyprinus carpio fish in Dohuk province, Iraq, where they obtained 39.1%.…”
Section: Discussionsupporting
confidence: 92%
“…As for the number of samples that gave positive results for the Stx1 gene from the local fish market, it was 25 samples at a rate of 89.3%. As for the Stx2 gene, the number of samples was 24 samples at a rate of 85.7%, while these results of Stx1 and of Stx2 were not detected and do not identify with another study conducted in Duhok Province/ Iraq (26), as well, the results of this study were higher than the results of Siddhnath et al (27), when they revealed the percentage 27% of the positive Stx genes detected by direct PCR. In his research, which he conducted on 18 fish samples, where 8 samples contained Sxt1 by 44% and 14 samples contained Stx2 by 77%, Ribeiro et al (28) revealed that out of the 115 isolates, 2 (1.74%) were positive only for the Stx1 gene and six isolates 5.21% for Stx2 gene.…”
Section: Discussioncontrasting
confidence: 89%
“…At the Bahir Dar municipal abattoir, 55.60% of carcass swab isolates were DEC, which is in accordance with the 52% DEC isolation recorded by Taha and Yasin [13]. The signi cant DEC contamination of the carcass observed in this study might originate from fecal contamination during the animal slaughtering process [13].…”
Section: Discussionsupporting
confidence: 89%